Polarized transilluminating dermoscopy: Bedside trichoscopic diagnosis of trichothiodystrophy. Issue 1 (25th September 2017) - Yang, Yul W.; Yarbrough, Kevin; Mitkov, Mario; Russi, Daniela; Price, Harper N.; Swanson, David L.
Abstract: Trichothiodystrophy is a rare autosomal recessive disorder resulting in a broad range of systemic abnormalities. Polarizing microscopy of the hair reveals the pathognomic "tiger tail" of alternating light and dark bands, but the need for a microscope prevents rapid bedside diagnosis. We describe a new technique for the bedside diagnosis of trichothiodystrophy using a handheld polarizing dermatoscope, precluding the need for microscopic examination.